Effect of case counseling on remission periods of synthetic cannabinoid addicts - Yusufoğlu, Yusuf; Bilici, Rabia; Arca, Muhammed (Journal of Dependence, 2022)
Objective: The aim of this study was to compare the remission periods of patients who receive case counseling service and those who are followed up without this service in the treatment of substance addiction. Method: The research was carried out in 2018 at the Health Sciences University Erenköy Mental and Neurological Diseases Training and Research Hospital. The study was conducted with a total of 80 synthetic cannabinoid addicted patients, 43 followed by the case counselors and 37 not followed. The patients included in the study were called for regular interviews and followed for 3 months. The Patient First Interview Form and Patient Followup Form, structured in line with the literature, were used to collect the data. Results: 60% of the patients were primary school graduates, 73.8% were single, 57.5% were not working and 93.8% lived with their families. 60% of all patients in the study met the criteria for early remission, and 40% experienced relapse. 76.7% of the patients served by the case counselors remained in remission and 23.3% experienced relapse. 40.5% of the patients who were not served by case counselors remained in remission and 59.5% experienced relapse. A statistically significant increase in remission rates was observed in patients followed up by case counselors compared to patients who were not followed. Conclusion: The patients followed up by the case counselors remained in remission at a higher rate than the patients who were not followed up. The longer remission period in the follow-up of the case counselor in the treatment of substance addiction indicates that such programs can be used in treatment and rehabilitation.